The Impact of Interactivity and Live Streaming Promotion (TikTok Shop) on Consumer Purchase Intention: An S-O-R Model Approach - Safira Putri; Yasyifa Dian Urfina; Fakhriansyah Fakhriansyah; Rifaid Rifaid (JURNAL ECONOMINA, 2026)
This study examines the impact of live streaming interactivity and promotion on consumer purchase intention in TikTok Shop through the Stimulus-Organism-Response (S-O-R) model, with trust and consumer attitude as mediating variables. Data were collected from 174 respondents in West Nusa Tenggara using purposive and snowball sampling techniques and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that interactivity does not have a direct effect on purchase intention but significantly influences purchase intention through the mediating role of trust. Meanwhile, promotion has a significant effect on purchase intention, both directly and indirectly through consumer attitude. The model explains 74.9% of the variance in consumer purchase intention. These findings highlight the importance of strengthening consumer trust and fostering positive attitudes as key strategies for enhancing live streaming marketing effectiveness on TikTok Shop.